High Fibrinogen Levels with Diabetes Mellitus are Associated with All-Cause and Cardiovascular Mortality in Patients with End-Stage Renal Disease and Acute Coronary Syndrome - Xie E; Wu Y; Ye Z; Gao Y; Zheng J (Dove Medical Press, 2024)
Enmin Xie,1,2 Yaxin Wu,3 Zixiang Ye,1,4 Yanxiang Gao,1 Jingang Zheng1,2 1Department of Cardiology, China-Japan Friendship Hospital, Beijing, People's Republic of China; 2China-Japan Friendship Hospital (Institute of Clinical Medical Sciences), Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People's Republic of China; 3Department of Cardiology, Henan Provincial People's Hospital, Fuwai Central China Cardiovascular Hospital, Zhengzhou, People's Republic of China; 4Department of Cardiology, Peking University China-Japan Friendship School of Clinical Medicine, Beijing, People's Republic of ChinaCorrespondence: Jingang Zheng, Department of Cardiology, China-Japan Friendship Hospital, 2 Yinghua Dongjie, Beijing, 100029, People's Republic of China, Email mdjingangzheng@yeah.netObjective: As a biomarker of inflammation and a core component in the coagulation pathway, fibrinogen contributes to atherosclerosis and subsequent adverse cardiovascular events and is modified by the occurrence of diabetes mellitus. However, the association between fibrinogen, diabetes status, and mortality in patients with end-stage renal disease (ESRD) and acute coronary syndrome (ACS) remains scarce.Methods: A multi-center cohort study enrolled 1079 patients with ESRD and ACS between January 2015 and June 2021. Patients were classified into three groups based on fibrinogen tertiles and were further categorized by diabetes status. The primary outcome was all-cause mortality, while the secondary outcome was cardiovascular mortality.Results: During a median 21.5 months of follow-up, 386 cases of all-cause mortality were recorded, including 262 cases of cardiovascular mortality. Multivariable Cox regression model revealed that patients with the third tertile of fibrinogen and those with diabetes experienced a significantly increased risk of all-cause mortality (fibrinogen: hazard ratio [HR], 1.70; 95% confidence interval [CI], 1.32- 2.19; diabetes: HR, 1.36; 95% CI, 1.10- 1.68). When patients were stratified by both fibrinogen levels and diabetes status, patients in the third fibrinogen tertile with diabetes had the highest risk of all-cause mortality (HR 2.43, 95% CI 1.69- 3.48) compared to those in the first fibrinogen tertile without diabetes. Similar associations were observed for cardiovascular mortality. Notably, incorporating the combined fibrinogen and diabetes status into the Global Registry of Acute Coronary Events (GRACE) score or baseline risk model led to significant improvements in the C-statistics for predicting mortality, surpassing the advancements achieved with any single biomarker.Conclusion: In patients with ESRD and ACS, elevated fibrinogen and diabetes were associated with an increased risk of all-cause and cardiovascular mortality. Categorizing patients based on fibrinogen levels and diabetes status could provide valuable information for risk stratification of these patients.Keywords: Acute coronary syndrome, Diabetes mellitus, End-stage renal disease, Fibrinogen, Prognosis